Immune-histochemical indicators of the morpho-functional state of the thyroid gland in norm and after prenatal antigenic exposure - Fedosieieva, O.V. (Medicni Perspektivi, 2021)
During the individual development and exposure to infectious agents of the organism, the structural components of the thyroid gland can change significantly. In modern research, great importance is attached to the study of mechanisms for maintaining morphological homeostasis of the thyroid gland and ideas about its structural and functional restructuring in response to the body’s immune system to various infections. The morpho-functional features of the thyroid gland of newborn animals after prenatal action of thyroid-nonspecific antigen (staphylococcal toxoid) have been experimentally established. In antigen-premiumed rats, the timing of folliculogenesis changes, as well as the size, distribution and immunohistochemical expression of antibodies to thyroglobulin, the functional state of thyrocytes and follicles compared to normal. The detected immunohistochemical changes indicate signs of morpho-functional immaturity of the organ with hypoactivity elements.